Bibliometric Analysis and Visualization of Global Ocean Acidification Research. Issue 4 (1st October 2020) - Sahoo, Sidhartha; Pandey, Shriram
ABSTRACT: This comprehensive study focuses on analyzing the growth of research in the domain of ocean acidification using various bibliometric methods. Datasets were retrieved from Scopus databases using keywords pertaining to the subjects, and detailed analysis was made to understand the growth of literature, publication trends, authorship pattern, keywords, country-wise distribution, and leading institutes working in the subject domain of ocean acidification. The resultant data show that a significant portion (37.83%) of the research documents are published in open-access journals. The finding shows that 76.06% of the total publication has published in the last seven years (2013–2019). In the year 2017, research in this subject reached its peak with the highest number of publications 697 (12.54%). The top 15 journals published around 34.04% (1, 891) of the entire research documents. GEOMAR Helmholtz Center for Ocean Research Kiel, Germany, has produced the highest number of research papers (5.42%) followed by Alfred Wegener Institute, Helmholtz Center for Polar and Marine Research, Germany (4.66%), and National Oceanic and Atmospheric Administration, the USA, with 4.39% of research documents. It has been found that Biogeosciences published by European Geosciences Union is the most preferred journal by researchers for publishing their work followed by Plos One covering around 215 (3.87%) papers and Marine Ecology Progress Series of 166 (2.99%) articles. A significant portion of the research documents are published in the sub-subject domain of Agricultural and Biological Sciences (55.31%), followed by Environmental Science (42.03%) and Earth and Planetary Sciences subject domains (37.99%). There has been an unparalleled growth of ocean acidification research during the last decade.